What stars are made of the life of Cecilia Payne-Gaposchkin - Moore, Donovan (Harvard University Press, 2020)
"Cecilia Payne-Gaposchkin was the revolutionary scientific thinker who discovered what stars are made of. But her name is hard to find alongside those of Hubble, Herschel, and other great astronomers. Donovan Moore tells the story of Payne's life of determination against all the obstacles a patriarchal society erected against her"--